The Effect of Work Ability and Motivation on Employee Performance in PT. Avesta Continental Pack Bekasi - Muratin Muratin; PJP Ginting (Budapest International Research and Critics University, 2022)
This research aims to determine whether the ability, and work motivation affect the performance of employees at PT. Avesta Continental Pack, on Jalan Raya Bekasi Km. 28.5 Bekasi; West Java. The research method used is descriptive quantitative with a questionnaire as a data source. The population in this study were employees of PT. Avesta Continental Pack totals 523 employees. The sample in this study were 84 respondents. The analytical tool in this study is multiple linear regression, the questionnaire data was analyzed using the SPSS version 17 program tool. The results showed that. there is a positive and significant effect on ability (X1) and motivation (X2) on employee performance variables (Y), this is proven by a significance level of 0.000 <0.05 then Ho is rejected and Ha accepted.